Energy system diagnosis of paper-drying process, Part 1: Energy performance assessment. Issue 8 (10th June 2016) - Chen, Xiaobin; Li, Jigeng; Liu, Huanbin; Yin, Yongjun; Hong, Mengna; Zeng, Zhiqiang
ABSTRACT: Paper drying is a highly energy-intensive and complicated multivariate process. The dryer section plays an important role in the energy consumption of a paper machine, especially of thermal energy. A comprehensive method for assessing the energy performance of the dryer section was investigated in this study to improve energy efficiency. This method was divided into three component processes: energy and evaporation load audit, field test and observation, and energy flow analysis and energy efficiency estimation. In a case study, we found that the method could, in addition to analyzing the key factors that restrict drying efficiency, also depict the details of energy consumption clearly. At the same time, several significant energy-saving measures were suggested to improve the energy efficiency of the paper-drying process.